Controversies about the use of mesh in the manage ment of pelvic floor problems - Brazão Júnior, Éder Silveira (2016)
Use of mesh for the treatment of pelvic organ prolapse is an excellent alternative especially in the treatment of the apical prolapse (uterine / vaginal vault) through an abdominal sacrocolpopexia; also in the anterior wall prolapse treated per vagina. There is no evidence to support use of mesh to correct posterior vaginal wall prolapse. Most important factors for favorable surgical outcome and to reduce mesh-associated complications are adequate selection of patients and a surgeon adequately trained for pelvic floor surgery.